Secondary Metabolite Profile in Stem and Root of Keji Plant (Staurogyne elongata [Blume] Kuntze) - Safitri, Hana; Malik, Abdul; Mukaromah, Arnia Sari (Universitas Brawijaya, 2024)
Keji (Staurogyne elongata [Blume] Kuntze) is an herbal medicinal plant that is often found on the Java to Sumatra islands. The leaves and roots of keji (S. elongata) have been used by the community as diuretic drugs, increasing blood pressure and trusted to treat bladder stones, kidney stones, and joint problems. However, research on secondary metabolites in the stems and roots of keji has never been done. The study aimed to identify the secondary metabolite content and marker compounds in the stems and roots of S. elongata. The research stages were drying and sample grinding, extraction, and metabolite compound analysis using Gas Chromatography-Mass Spectrometry (GC-MS). The results showed nine secondary metabolite compounds found in S. elongata stem, such as phenol, terpenoid, and alcohol. Meanwhile, secondary metabolite compounds of S. elongata root were ten compounds from the coumaran, phenols, and ester group. The 2,2’-methylenebis[6-(1,1-dimethylethyl)-4-methyl-phenol is proposed as a marker compound in S. elongata stem. Meanwhile, no secondary metabolites can be used as marker compounds in S. elongata roots because octadecanoic acid, 2-hydroxy-1-(hydroxymethyl)ethyl ester is the primary metabolite.